ANALISIS TENTANG KEPUASAN PENGUNJUNG DI TAMAN MARGASATWA SEMARANG - Wahma Dewi Bintari; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Semarang Wildlife Park is a place that combines the concept of conservation, education and recreation that be equipped with various supporting facilities should be managed optimally in order to attract tourist’s interests and to produce tourist’s satisfactions. Satisfaction is a perception or a result of opinion and public appraisal on service performance which is given by apparatus of public service provider. This research aims to know the level of visitor’s satisfactions and the suitability of visitor’s expectations toward the service performance in Semarang Wildlife Park. The theory used was PERMENPAN-RB No. 16 year 2014 about Public Satisfaction Surveys on Public Service Management by referring to the nine existing elements that are requirement, procedure, service time, cost/ tariff, product specification type of service, executor competence, executor behavior, service announcement, handling complaint, suggestion and input. It also used the dimension theory of service quality according to Zeithaml et al by referring to five elements that are tangibles, reliability, responsiveness, assurance and empathy. The method used in this research was descriptive quantitative and to know the elements that determine the level of visitor’s satisfactions used Cartesian Diagram. The results of the research showed that from 14 indicators there were 5 indicators that were included in satisfactory category such as requirement, procedure, service time, cost/ tariff, and executor behavior. There are seven indicators that were included in the quite satisfactory category such as the product specification type of service, executor competence, service announcement, reliability, responsiveness, assurance, and empathy. There are two indicators that were included in the less satisfactory category such as handling complaint, suggestion and input indicators and alsotangible indicator.